Reformulating the Business Model Canvas: Integrating Success Determinants of the Hotel Industry - Ardiaz Ajie Aryandika; Dhena Kamila Fu’adi (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2025)
This study investigates how the Business Model Canvas can be reconfigured for the hotel industry by embedding critical success determinants specific to hotel operations. While the conventional canvas offers a general framework for describing value creation, delivery, and capture, it does not fully capture the operational dynamics that shape performance in hospitality businesses. To address this gap, the research combines primary data obtained through in-depth interviews with hotel managers and secondary data drawn from an extensive review of hospitality and business-model literature. The analysis identifies additional elements—covering strategic location, workforce empowerment, and both internal and external marketing orientation—that extend the nine original building blocks of the canvas. The resulting framework is intended to provide hotel owners and managers with a more contextually grounded tool for formulating competitive strategies, strengthening customer relationships, and maximizing revenue performance across diverse hotel segments.